50 years of Indian republic - Santhanam, M K (Ed.); India. Ministry of Information and Broadcasting Publications Divisions (New Delhi Publication Division, 2000)
50 years of Indian Republic is a compilation of articles on India's nation-building efforts since it become a republic in 1950.The contents coversvarious facets of development such as Indian economy,agriculture,science and technology,poverty alleviation,e
Keywords: India-Politics and government; India-Economic conditions; Democracy; India-Foreign policy